What could health technology assessment learn from living clinical practice guidelines? - Cheyne, Saskia; Chakraborty, Samantha; Lewis, Samara; Campbell, Sue; Turner, Tari; Norris, Sarah (Frontiers in Pharmacology, 2023)
A ‘living’ approach to clinical practice guidelines is when the identification, appraisal and synthesis of evidence is maintained and repeated at an agreed frequency, with a clear process for when and how new evidence is to be incorporated. The value of a living approach to guidelines was emphasised during the COVID-19 pandemic when health professionals and policy makers needed to make decisions regarding patient care in the context of a nascent but rapidly evolving evidence base. In this perspective, we draw on our recent experience developing Australian and international living guidelines and reflect on the feasibility of applying living guideline methods and processes to a lifecycle approach to health technology assessment (HTA). We believe the opportunities and challenges of adopting a living approach in HTA fall into five key themes: identification, appraisal and synthesis of evidence; optimising the frequency of updates; embedding ongoing multi-stakeholder engagement; linking the emergence of new evidence to reimbursement; and system capacity to support a living approach. We acknowledge that the suitability of specific living approaches to HTA will be heavily influenced by the type of health technology, its intended use in the health system, local reimbursement pathways, and other policy settings. But we believe that the methods and processes applied successfully to guideline development to manage evidentiary uncertainty could be applied in the context of HTA and reimbursement decision-making to help manage similar sources of uncertainty.